DEVELOPMENT OF VIDEO MEDIA FOR LEARNING THE VALUES OF H.O.S TJOKROAMINOTO'S FIGURE TO IMPROVE THE MOTIVATION OF LEARNING HISTORY OF GRADE XI STUDENTS OF SMA IT BANGKINANG: PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN NILAI-NILAI KETOKOHAN H.O.S TJOKROAMINOTO UNTUK MENINGKATKAN MOTIVASI BELAJAR SEJARAH SISWA KELAS XI SMA IT BANGKINANG - Firdaus; Isjoni; Asril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Education is an effort to build the next generation of the nation. In education, teachers are directed to guide and encourage their students to be more serious and motivated, so that students do not feel lazy in learning. Not only that, teachers as educators are also required to innovate in building students' interest in learning. This innovation is done so that explanations related to learning are not only using the same methods and media, but also different ones, so that students do not feel bored. In this study, the researcher develops a teaching media in the form of learning videos related to the values of H.O.S Tjokroaminoto's figure to increase the learning motivation of 11th-grade students at SMA IT Bangkinang